PRE CONCEPTIONAL CARE : AN INTEGRATED APPROACH WITH AYURVEDA - Tekam, Vishwanath Singh; Bharathi, K; Pushpalatha, B (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda, the philosophical knowledge of life takes care of all aspects of human well being and adopting it is a valuable first step towards becoming a truly integrated individual, it gives great importance for the pre conceptional care which includes preparing the body of both individuals, rather than post conceptional care so as to ensure a healthy and successful progeny, The Ayurveda preconceptional care begins with selection of the right partner, both constitutional and age wise. It then explains about the right mode of conception and the importance of food and water in establishing a firm foundation from the very beginning of pregnancy.